KEANEKARAGAMAN JENIS MAMALIA DI ARBORETUM UNIVERSITAS RIAU KOTA PEKANBARU PROVINSI RIAU - Dwi Seprina; Defri Yoza; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Arboretum of Riau Universityis a habitat whom build a one connectionpotential habitat for wildlife and more organism. As a supporting tool that provides useful information for various purposes, booth in terms of education, social, economicand ecology. It is necessary to support the complete data by conducting research on the animals in the Arboretum of Riau University, especially mammals, to find out the large index of diversity and richness of mammals species contained in Arboretum of Riau University. This Research held on November 2016 until January 2017. Method used for this research is a line transectsmethod and trap.On research location obtained result isthere 9 of mammals from 6 family founded with 63 individual that founded. The index of species diversity in both dry line (1,93) and wet line (1,73) was moderate. Richness index varieties dry line  (1,97) wet line(1,80)  is low.Most of mammals on Arboretum of Riau University are animals living on forest floor  (teresterial), small flying mammals are met for while research only bats  and kind of living animals on canopy area crown and the middle of the canopy crown (arboreal).  Keywords: Mammals, Diversity, Arboretum